2021
DOI: 10.4062/biomolther.2021.143
|View full text |Cite
|
Sign up to set email alerts
|

Podophyllotoxin Induces ROS-Mediated Apoptosis and Cell Cycle Arrest in Human Colorectal Cancer Cells via p38 MAPK Signaling

Abstract: Podophyllotoxin (PT), a lignan compound from the roots and rhizomes of Podophyllum peltatum, has diverse pharmacological activities including anticancer effect in several types of cancer. The molecular mechanism of the anticancer effects of PT on colorectal cancer cells has not been reported yet. In this study, we sought to evaluate the anticancer effect of PT on human colorectal cancer HCT116 cells and identify the detailed molecular mechanism. PT inhibited the growth of cells and colony formation in a concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 45 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Regulating intracellular ROS status could proficiently kill tumor cells and suppress the adverse effects of radio/chemotherapy, and it is presently regarded as the primary means of tumor management (35). Several previous studies already demonstrated that many natural compounds are well known to increase the intracellular ROS production and lead to cell death in cancer cells (36)(37)(38). Likewise, we found that the ononin treatment substantially augmented the intracellular ROS status in the Hep-2 cells, thereby leading to oxidative stress mediated cell death (Figure 2B).…”
Section: Discussionmentioning
confidence: 99%
“…Regulating intracellular ROS status could proficiently kill tumor cells and suppress the adverse effects of radio/chemotherapy, and it is presently regarded as the primary means of tumor management (35). Several previous studies already demonstrated that many natural compounds are well known to increase the intracellular ROS production and lead to cell death in cancer cells (36)(37)(38). Likewise, we found that the ononin treatment substantially augmented the intracellular ROS status in the Hep-2 cells, thereby leading to oxidative stress mediated cell death (Figure 2B).…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Lee evaluated the anticancer mechanism of PTOX on human colorectal cancer and found that it could induce cell cycle arrest in the G2/M phase and apoptosis through the p38 MAPK signalling pathway by upregulating reactive oxygen species (ROS) in HCT116 cells. 90 However, more applications of PTOX deal with its structural derivatives.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“… AOM/DSS induced CRC model mice Proliferation ↓, inflammation ↓, Angiogenesis ↓, Invasion ↓ ↓: Ki-67, β-catenin, IL-1b, TNF-α, NF-κB, MMP9, Ereg, Muc16 NF-κB [ 74 ] Curcumin Jiang Huang ( Curcuma longa L.) HCT-116、SW620、HT-29 HCT-116 orthotopic mice Proliferation ↓, Invasion ↓, Angiogenesis ↓, Apoptosis ↑ ↓: NF-κB, COX2, Cyclin D1, c-myc, MMP9, ICAM-1, CXCR4, survivin, Bcl-2, VEGF NF-κB [ 75 ] Ginsenoside Rh1 (Rh1) Ren Shen ( Panax ginseng C.A.Mey.) SW620 Proliferation ↓, Migration ↓, Invasion ↓ ↑: TIMP3 ↓: MMP1, MMP3, p-P38/P38, p-ERK1/2/ERK1-2, p-JNK/JNK MAPK [ 94 ] SW620 xenograft mice Tumor growth ↓ ↓: p-P38/P38, p-ERK1/2/ERK1-2, p-JNK/JNK Diterpenoid C Jiang Huang ( Curcuma longa L.) SW620 Proliferation ↓, Apoptosis ↑ ↑: caspase-3 ↓: p-ERK, p-JNK, p-p38 MAPK MAPK [ 96 ] Podophyllotoxin (PT) Gui Jiu ( Podophyllum peltatum ) HCT-116 Apoptosis ↑, Block cell cycle ↑: ROS, GRP78, CHOP, p38 MAPK p38 MAPK [ 100 ] Emodin (EMD) Da Huang ( Rheum palmatum L.) SW620、SW480 Apoptosis ↑, Migration ↓, Invasion ↓ …”
Section: Discussionmentioning
confidence: 99%
“…Podophyllotoxin (PT) is an active ingredient extracted from Podophyllum peltatum (Gui Jiu), which is highly cytotoxic to various cancer cells [97][98][99]. Lee et al [100] found that PT intervention increased the level of reactive oxygen species (ROS), upregulated the expression of ER stress markers GRP78 and CHOP, and increased the phosphorylation of p38 MAPK in HCT-116 cells, suggesting that PT could induce the p38 MAPK signaling pathway and ER stress-mediated apoptosis through upregulation of ROS in HCT-116 cells, accompanied by G2/M phase cell-cycle arrest (Fig. 3).…”
Section: Mitogen-activated Protein Kinase (Mapk) Signaling Pathwaymentioning
confidence: 99%